UDP-sugars activate P2Y 14 receptors to mediate vasoconstriction of the porcine coronary artery - Abbas, Zainab S.B.; Liaque Latif, M.; Dovlatova, Natalia; Fox, Sue C.; Heptinstall, Stan; Dunn, William R.; Ralevic, Vera (Elsevier, 2018)
Aims